Value creation in university‐firm research collaborations: A matching approach - Mindruta, Denisa (Strategic Management Journal, 2013)
The article discusses the interface between corporate entrepreneurship and academic research. Collaborative university-industry research alliances have been found to create value in terms of patents, products and sales growth. Strategic considerations for partnership formation are analyzed. Two-sided matching theory is used to characterize these alliances as endogenous matching processes. Factors such as technological and scientific capabilities, specialization and knowledge breadth are also discussed.